2019
DOI: 10.4236/ojog.2019.92019
|View full text |Cite
|
Sign up to set email alerts
|

The Area under the Curve (AUC) of Oral Glucose Tolerance Test (OGTT) Could Be a Measure Method of Hyperglycemia in All Pregnant Women

Abstract: Objective: We adopted the area under the curve (AUC) of oral glucose tolerance test (OGTT) as a measure method of the severity of maternal hyperglycemia and investigated its relationship with adverse perinatal outcomes among women with and without gestational diabetes mellitus (GDM). Research design and methods: This is a retrospective cohort study. Our study group collected the medical records of 15,296 women who received perinatal care in 15 hospitals in Beijing and who delivered from July 1, 2013, to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…In the current study, we conducted fixed-effects meta-analyses of EWAS investigating associations between continuous maternal glucose, insulin, and area under the curve of glucose (AUC gluc ) measures from an oral glucose tolerance tests (OGTT) conducted during pregnancy and cord blood DNAm. We used AUC gluc as one of our exposures of interest, as glucose measures at different OGTT time points show similar linear associations with health outcomes ( 1 ) and capture both fasting and nonfasting maternal glycemic regulation ( 10 ). The findings from the meta-analyses were subsequently looked up in complementary observational studies for assessment of whether the variation of DNAm at identified CpGs also potentially associated with cardiometabolic traits in children ( 11 ) and adults ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we conducted fixed-effects meta-analyses of EWAS investigating associations between continuous maternal glucose, insulin, and area under the curve of glucose (AUC gluc ) measures from an oral glucose tolerance tests (OGTT) conducted during pregnancy and cord blood DNAm. We used AUC gluc as one of our exposures of interest, as glucose measures at different OGTT time points show similar linear associations with health outcomes ( 1 ) and capture both fasting and nonfasting maternal glycemic regulation ( 10 ). The findings from the meta-analyses were subsequently looked up in complementary observational studies for assessment of whether the variation of DNAm at identified CpGs also potentially associated with cardiometabolic traits in children ( 11 ) and adults ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during a 7‐year follow‐up of first‐degree relatives of type 2 diabetic patients, G‐AUC levels were highly predictive of the future risk of developing diabetes 23 . Another study suggested that G‐AUC may be a measure of gestational diabetes 24 . Interestingly, a recent analysis suggested that pre‐infection glucose control was associated with a risk for severe respiratory complications in COVID‐19 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Another study suggested that G-AUC may be a measure of gestational diabetes. 24 Interestingly, a recent analysis suggested that pre-infection glucose control was associated with a risk for severe respiratory complications in COVID-19. 25 The data from the current study suggests that glucose AUC may be more sensitive to glycemic abnormalities than standard OGTT alone.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 23 ] reported that the AUC for the 100-g OGTT was associated with an increased risk of LGA in GDM. Another study from China demonstrated that a higher AUC for the 75-g OGTT was related to adverse pregnancy outcomes, such as hypertensive disease and macrosomia [ 24 ]. Our study findings are consistent with these results, demonstrating that hyperglycemia itself is an important pitfall for adverse perinatal outcomes though a more meticulous analysis of the OGTT results.…”
Section: Discussionmentioning
confidence: 99%